Soil organic carbon stock is improved by cover crops in a tropical sandy soil - Cordeiro, Carlos Felipe dos Santos [UNESP]; Rodrigues, Daniel Rodela; Silva, Gustavo Ferreira da [UNESP]; Echer, Fábio Rafael; Calonego, Juliano Carlos [UNESP] (Wiley, 2022)
Soil organic matter plays an important role in soil quality. In sandy soils of tropical regions, high biological activity in the soil accelerates mineralization and limits increases in organic matter content. The objective of this study was to evaluate the total organic C stock and the chemical and physical fractions of organic C in a sandy soil in Presidente Bernardes, São Paulo, Brazil, as a function of cover cropping with different combinations of grasses and legumes between 2015 and 2020. The treatments comprised fallow (control), cultivation of a single grass or intercropping of two grasses, one grass and one legume, or a mixture of two grasses and one legume during the offseason (April–September). Intercropping two grasses increased total dry matter production (shoot and root) by 138% and decreased the C/N ratio by 19% compared with the fallow and legume systems. The organic C stock in the soil was 46% higher in the mixed cover crop system (36.5 Mg ha−1) than in the fallow system (25 Mg ha−1). Humic acid (0.78–0.82 g kg−1) and humin (1.68–1.99 g kg−1) were lower in the systems with low dry matter production (fallow and grass + legume). Mineral-associated C content was 114% higher in the mixed cover crop system than in the fallow system. These results show that cover crops can increase C content in all fractions of organic matter in tropical sandy soil, even in a short period of time (5 yr), and that a mix of cover crops is the best option.